Is Gift-Giving the Core of Existential Therapy? A Discussion with Irvin D. Yalom (Existential Analysis: Journal of the Society for Existential Analysis, 2003)
Irvin D.Yalom's work on existential therapy is being read and discussed all over the world. There are a number of ways to interpret his work. Yalom does not travel in Europe, so Bo Jacobsen from the University of Copenhagen went to California to clear up a number of points in the interpretation of Yalom's work. The discussion takes its point of departure in Yalom's new book The Gift of Therapy but also takes up a number of issues from his main work Existential Psychotherapy.